Konsep Pendidikan Generasi Penerus dalam Pemikiran Muhammadiyah: Kajian Pustaka Kritis - A Ansorullah; Daud Ridwan; Siti Qomariatul Munawaroh; Heri Rifhan Halili (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2025)
This study aims to critically examine the concept of successor generation education in Muhammadiyah thought as part of the tajdid movement and the project of modern Islamic civilization building. This research employs a library research approach with qualitative- interpretative analysis of primary and secondary sources, including official Muhammadiyah documents, works of prominent figures, and contemporary scholarly literature. Data analysis is conducted through content analysis with emphasis on thematic coding and conceptual reconstruction. The findings reveal that Muhammadiyah’s educational concept is holistic, integrative, and transformative, integrating the values of tawhid, rationality, morality, and social responsibility. Education is not merely understood as the transmission of knowledge, but as a systematic effort to shape faithful, knowledgeable, ethical, and socially responsible individuals who are capable of responding to global challenges. The novelty of this study lies in positioning successor education as Muhammadiyah’s long-term ideological and strategic vision oriented toward civilizational development rather than merely institutional practice. This study confirms that Muhammadiyah’s educational model has strong potential to serve as a reference for the development of progressive, moderate, and inclusive Islamic education.